SGLT2i and GLP1-RA exert additive cardiorenal protection with a RAS blocker in uninephrectomized db/db mice - Martos-Guillami, Nerea; Vergara, Ander; Llorens-Cebrià, Carmen; Motto, Aku Enam; Martínez-Díaz, Irene; Gonçalves, Francisco; Garcias-Ramis, Maria Magdalena; Allo-Urzainqui, Estibaliz; Narváez, Alonso; Bermejo, Sheila; Muñoz, Vicent; León-Román, Juan; et al. (Frontiers in Pharmacology, 2024)
Diabetic Kidney Disease (DKD) is the main cause of end-stage renal disease in the developed world. The current treatment of the DKD with renin-angiotensin system (RAS) blockade does not totally halt the progression to end stage kidney disease. Currently, several drugs have shown to delay DKD progression such as sodium-glucose co-transporter-2 inhibitors (SGLT2i) and glucagon-like-1 receptor agonists (GLP-1RA). We hypothesized that by combining several drugs that prevent DKD progression on top of RAS blockade a synergistic effect would be achieved in terms of cardiorenal protection. In the present study, we analysed if the combination of a RAS blocker (ramipril) with a SGLT2i (empagliflozin) and/or GLP-1RA (semaglutide) in a type 2 diabetic mouse model could have add-on effects in kidney and heart protection. Male and female uninephrectomized type 2 diabetic db/db mice were treated with empagliflozin and/or semaglutide on top of ramipril during 8 weeks. During the study body weight, water and food intake were weekly monitored, glycaemia biweekly and albuminuria and glomerular filtration rate (GFR) before and after the treatment. At the end of the experiment, kidney and heart were isolated for histological and gene expression studies as well as for intrarenal RAS state assessment. Semaglutide combined with ramipril and/or empagliflozin significantly decreased albuminuria but only when combined with both compounds, semaglutide further decreased blood glucose, glomerular hyperfiltration in male mice and glomerular mesangial matrix expansion. In kidney, only the triple treatment with empagliflozin, semaglutide and ramipril reduced the expression of the proinflammatory and profibrotic genes ccl2 and TGFß1. In addition, the combination of empagliflozin and semaglutide on top of RAS blockade was superior in decreasing cardiomyocyte hypertrophy and heart fibrosis in db/db mice. Our results suggest that the combination of SGLT2i with GLP-1RA is superior in cardiorenal protection in DKD than the drugs administered alone on top of RAS blockade.